Phenethylamine‐Based Interfacial Dipole Engineering for High Voc Triple‐Cation Perovskite Solar Cells. Issue 1 (16th November 2021) - Kim, Gyu Min; Sato, Hiroshi; Ohkura, Yuya; Ishii, Ayumi; Miyasaka, Tsutomu
Abstract: Surface modification of 3D hybrid perovskites using 2D perovskites, such as phenethylamine halides (PEAX), increases the overall power conversion efficiency (PCE) and stability of perovskite solar cells (PSCs). The effect is based on a surface passivation phenomenon where PEAX is in direct contact with the perovskite and hole transport layer (HTL). However, it is herein observed that the PCE of PSCs containing PEAX increases significantly when they are not in direct contact with either the bottom layers (perovskites) or top layers (HTLs). Moreover, the highest PCE (>22%) is obtained for the PSCs when PEAX is not in contact with HTLs by using poly(methyl methacrylate) (PMMA). Photoemission measurements reveal that the shift of the highest occupied molecular orbital of the hole transporting material (a donor‐acceptor‐donor molecule synthesized for the study) to a deeper level results in an increased hole transfer at the perovskite/HTL interface leading to an improved device performance. It is proposed that PEAX acts as dipoles aligned between perovskite and HTL resulting in a shift in the energy levels. The combination of PEAX/PMMA at the interface enables high open‐circuit voltage (1.19V) close to the Shockley–Queisser limit for the triple‐cation (Cs‐MA‐FA) perovskites (bandgap, 1.51 eV). Abstract : Phenethylamine halides (PEAX) coated on perovskite layers either form 2D perovskites or dipole moments. High‐performance perovskite solar cells are realized mainly due to the formation of dipole moments caused by PEAX leading to high open‐circuit voltages. This implies that direct contact of PEAX with the perovskite layer is not necessary for further improvements.